2013
DOI: 10.2196/jmir.2350
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a Multidimensional iPhone Pain Assessment Application for Adolescents with Cancer

Abstract: BackgroundPain is one of the most common and distressing symptoms reported by adolescents with cancer. Despite advancements in pain assessment and management research, pain due to cancer and/or its treatments continues to be poorly managed. Our research group has developed a native iPhone application (app) called Pain Squad to tackle the problem of poorly managed pain in the adolescent with cancer group. The app functions as an electronic pain diary and is unique in its ability to collect data on pain intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
227
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(237 citation statements)
references
References 35 publications
6
227
1
3
Order By: Relevance
“…[16][17][18]24,[28][29][30][31][32][33][34][35][36][37][38][39][40] In Box 3, we have highlighted several programs. An additional program, OCFighter, is described in detail in Box 4.…”
Section: What Resources Are Available For Internet-delivered Cbt?mentioning
confidence: 99%
“…[16][17][18]24,[28][29][30][31][32][33][34][35][36][37][38][39][40] In Box 3, we have highlighted several programs. An additional program, OCFighter, is described in detail in Box 4.…”
Section: What Resources Are Available For Internet-delivered Cbt?mentioning
confidence: 99%
“…4 An analysis of the Brazilian scientific production about pediatric cancer, published between 2000 and 2009, indicated the need for further research on the experience of adolescents with cancer, 7 which is significantly permeated by painful experiences. 8 Adolescence is a period of intense physical, psychological and social development, during which the adolescents gain further responsibility and autonomy, becoming increasingly dependent on the caregivers. 9 It is considered that, due to this greater independence, the adolescents themselves are the best source of information about their painful experience related to the cancer and its treatment, as well as effective strategies to relieve their pain, contributing to the excellence of cancer pain management.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all patients reported that they found the mobile interventions easy to use, regardless of age, cancer type and experience with technology [28,35,36,38,39,40,43,[45][46][47]. For example, Head and colleagues [35] reported that all 44 patients from the intervention arm of an RCT reported a handheld device to be very easy (85%) or easy (15%) to use.…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…Studies generally reported high adherence rates to the mobile interventions, regardless of the length of the study [28,30,31,35,43,44,45,[47][48][49]. A pilot RCT of 44 patients reported that patients used a handheld device consistently for an average of 10 weeks [35].…”
Section: Adherence To Mobile Interventionsmentioning
confidence: 99%